GEOSTATISTICS APPLIED TO AGROECOLOGY: SPATIAL AUTOCORRELATION BETWEEN FAMILY FARMING AND TECHNICAL ASSISTANCE IN THE STATE OF MARANHÃO (REMUNOM, 2024)
Brazilian family farming plays an indispensable role, whether in the production of healthier foods or in employing people. Where it makes a strong contribution to the conservation of biodiversity. In addition, it generates decent work in the field, thus strengthening family farming, and providing even greater autonomy for farmers in relation to consumer markets. The agroecological production system aims to strengthen organizations formed by family farmers, agrarian reform settlers, quilombola communities, indigenous peoples, and traditional extractive populations, among other movements that support the development of sustainable agriculture. The use technologies, especially GIS (Geographic Information Systems) in agriculture, whether familiar or not, contributes to a quick and accurate assessment, considering that assessing the sustainability of agroecosystems is a complex task. In this sense, the present research aims to spatially correlate technical assistance and family farming data from the 217 municipalities of the state of Maranhão obtained through the agricultural censuses of the years 2006 and 2017, through geostatistics, in particular, the technique Local Indicator of Spatial Autocorrelation, proposed by Anselin. For this purpose, data from technical assistance and family farming were used, through the software Microsoft Excel 2013 version 15.0.4805.1003 and GeoDa 1.20, the finalization of the map took place in the software GIS (Geographic Information System) Arcgis 10.8.1 trial version. As a final result, it was possible to infer that family farming lacks public policies that encourage education in the countryside and provide quality technical assistance to farmers.